INDONESIAN CRIMINAL LAW REFORM IN THE FACE OF CYBERCRIME - Loso Judijanto; Melyana R Pugu; Yuarini Wahyu Pertiwi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Criminal law reform in the face of cybercrime is a critical issue that requires attention in Indonesia. The research method used in this study is literature review. The purpose of this study is to evaluate the effectiveness of the current ITE Law and identify aspects that require improvement to optimise law enforcement against cybercrime. The results show that the current ITE Law requires adjustments to include more specific definitions and clear boundaries to avoid multiple interpretations and misuse. There is a need to update and enhance the law with higher standards related to human rights and freedom of expression. In addition, Indonesia's information technology infrastructure and human resources require improvement through investment and training to effectively address cybercrime challenges. International cooperation is also an important element of this research, which concludes that Indonesia should participate more actively in inter-state conventions and cooperation to strengthen its response to cross- border cybercrime. Therefore, this research suggests that legal reform, capacity building, and international cooperation are necessary to support Indonesia's efforts in dealing with cybercrime.